Large and lasting regional disparities in municipal investments - Felix Arnold; Ronny Freier; René Geissler; Philipp Schrauth (DIW Economic Bulletin, 2015)
The regional dispersion of local public investment in Germany is very uneven. Even a comparison between the states shows considerable differences in gross investment. Municipalities in Bavaria currently invest more than three times as much per capita as those in Mecklenburg-Western Pomerania. There are even greater differences between districts and independent cities, both nationwide and within the federal states. In 2013, the district of Munich invested 724 euros per inhabitant, in other words, almost 700 euros more than the independent city of Wilhelmshaven in Lower Saxony (35 euros per inhabitant). There are disparities within Bavaria, too, with the independent city of Weiden spending 560 euros less (160 euros per inhabitant) than the district of Munich. Our analysis demonstrates that there have been virtually no changes in the regional dispersion of investment spending over time. Around 83 percent of the weakest quartile of all municipalities in 2000 were still in the lower half of the distribution 14 years later. Overall, investment in economically strong municipalities is considerably higher than in the structurally weak regions. The level of investment has a positive correlation with high tax revenues and a negative one with high social security spending, a negative fiscal balance, and high levels of debt. Municipalities that are less competitive today will continue to struggle in the long term due to a lack of investment. This compounds differences in infrastructure and quality of location which are important general conditions for future economic performance.
Keywords: H10; H41; H72; 330; local public investment; regional dispersion; inequality